Husserl on Hume - Janousek, H; Zahavi, D (Taylor and Francis, 2019)
This article offers an account of the development of Husserl’s assessment of Hume’s position in the history of philosophy. In Husserl’s early treatment of Hume, Husserl’s interpretation was shaped by the anti-Kantian views of his teacher Franz Brentano. Later, however, Husserl concentrated on those themes in Hume’s philosophy that were of relevance for the development of his own conception of phenomenology. His analysis into the a priori structures of intentionality led the Husserl of Logical Investigations (1900-1901) to reject Hume’s nominalism and sensualism, and to criticize Hume’s naturalistic psychologism and fictionalism. Already at this point, however, Husserl appreciated Hume’s metaphysical neutrality as well as his radical starting point in the immediate givenness of consciousness. In the period following Husserl’s transcendental turn in Ideas I (1913), Hume is gradually re-assessed in the context of Husserl’s engagement with Kant as a philosopher who offers important insights concerning concrete problems of transcendental philosophy. For Husserl, Hume ultimately offers the first outline of a pure phenomenology and, indeed, becomes one of the most important forerunners of transcendental philosophy as such.